A global methane model for rice cropping systems: Final Report - Nikolaisen, Marte; Nayak, Dali Rani; Smith, Pete; Hillier, Jon; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
It has been estimated that rice production accounts for up to 55% of the total greenhouse gas (GHG) emissions budget from agricultural soils. Finding efficient ways to mitigate these emissions without adversely impacting yield is crucial as rice is a major cereal crop for half of the world’s population and with production being estimated to increase by up to 40% by 2040 to meet demands. Emissions are challenging to measure and thus finding field-specific mitigation options is difficult; many therefore rely on GHG tools to explore suitable mitigation strategies. We have collected field data from across the world from peer- reviewed publications pre-2021, by evaluating the influence of different factors on methane (CH4) fluxes, and using a step-down approach, a new CH4 model was created using the linear mixed model in Rstudio. The new model has five additional factors and uses a different climate classification compared to existing models. Baseline emission factors (EFs) were estimated using the predicted data. Result shows that the difference between tropical and temperate regions needs to be considered when calculating an EF. By having different pre- season water management as a baseline, more accurate EFs can be estimated, particularly for temperate and American rice regions as the existing EF uses a baseline of short drainage, which is not common in these regions that typically have a long drainage duration and only one rice crop cycle per year. Evaluation of the new model against existing models shows the new model performs better, with R values of 0.602 while other models produce R2 in the range of 0.11-0.37. The new model could be more sensitive to capture management practice differences between tropical and temperate rice and their impact on CH4 emission.